2016
DOI: 10.1016/j.precamres.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of ultramafics in the Neoarchean Veligallu greenstone terrane, eastern Dharwar craton, India: Constraints from bulk-rock geochemistry and Lu-Hf isotopes

Abstract: We report on the bulk-rock geochemistry and Lu-Hf isotope systematics, and infer the petrogenesis of the ultramafic rocks in the Neoarchean Veligallu greenstone terrane, eastern Dharwar craton, India. The ultramafics along with the basalts and adakites yield an age of 2.696 ± 0.054 Ga, consistent with the available SIMS zircon U-Pb age of 2.697 ± 5 Ma, reported for the felsic volcanics, in the literature. The rocks have positive initial εHf (2.696 Ga) = + 3.0 to + 6.5, consistent with an origin from a long ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 77 publications
(125 reference statements)
1
5
0
Order By: Relevance
“…Precision and accuracy are better than the RSD 3% for the majority of the trace elements. The major and trace element concentrations determined for BHVO-1 are in concurrence with the recommended values in the GEOREM database [16]. An independent analysis of international certified reference material BIR-1, (supplied by United States Geological Survey, Reston, VA, USA), which was run as an unknown, and not part of the calibration, is also provided in Table 4.…”
Section: Sampling and Analytical Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…Precision and accuracy are better than the RSD 3% for the majority of the trace elements. The major and trace element concentrations determined for BHVO-1 are in concurrence with the recommended values in the GEOREM database [16]. An independent analysis of international certified reference material BIR-1, (supplied by United States Geological Survey, Reston, VA, USA), which was run as an unknown, and not part of the calibration, is also provided in Table 4.…”
Section: Sampling and Analytical Methodssupporting
confidence: 66%
“…Besides the boninitic rocks reported here from the~3.3 Ga Holenarsipur greenstone belt, boninite-like rocks have also been recognized in the greenstone terranes of Eo-, Meso-and Neoarchean age [5][6][7][8]16]. The origin of boninites, in general, is attributed to a two stage melting process involving depletion of a mantle source due to prior melt extraction events, presumably at a mid-oceanic ridge, in the first stage, followed by partial melting of this depleted source triggered by the fluids/melts derived from the dehydration of subducted altered oceanic crust in the sub-arc mantle, in the second stage.…”
Section: Petrogenetic Implicationsmentioning
confidence: 99%
“…The total REE value of the Katpal ultramafics showed a narrow range of variation from 2.56 to 21.50 ppm, with there was limited REE fractionation. The (Ce/Yb) CN ratios varied from 0.77 to 4.79, LREE values varied from (La/Sm) CN = 0.79 to 3.17 [46], Nuasahi boninite [9], Bababudan komatiite [47], Veligallu ultramafic [48], Sonakhan SHMB [49], Barberton komatiite [50], Pilbara SHMB [51], and Isua boninite cumulate [52]. Bababudan komatiite [47], Veligallu ultramafic [48], Sonakhan SHMB [49], Barberton komatiite [50],…”
Section: Trace-element Geochemistrymentioning
confidence: 99%
“…The data of the Sukinda ultramafic complex are plotted along with different high-Mg rocks of the world for comparison purposes. The data are obtained after Gadwal boninite [103]; OMG boninite [46]; Bastar boninite [104]; Dongargarh boninite [105]; Nuasahi ultramafic [9]; Veligallu ultramafics [48]; Cape Vogel boninite [106], and Isua boninite cumulate [52].…”
Section: Classification and Parent Melt Compositionmentioning
confidence: 99%
“…Existence of an ancient subduction event in the Dharwar craton is established through several geochemical and isotopic studies on felsic and mafic volcanic rocks from the Neoarchean greenstone belts (e.g., Manikyamba et al 2005;Ram Mohan et al 2013;Khanna et al 2015Khanna et al , 2016. It is suggested that these Neoarchean felsic (adakiticaffinities and Mg-andesites) and mafic (boninitelike ultramafics) volcanic rocks have their genesis through subduction tectonics.…”
Section: Decoding Alaskan-type Signature Of the Pulivnedla Ultramaficmentioning
confidence: 99%